التفسير التحليلي للآيات (1-8) من سورة الأنعام: دراسة نموذجية - Mannan, Anamul Hoque Abdul (Darul Yasin Al Sys, 2025)
This research addresses a type of interpretation: analytical interpretation. This study aims to uncover the secrets of the close connection between the Qur'anic verses in the blessed Surah Al-An'am, from verse (1) to verse (8), and the gems and pearls they contain, using an analytical and inductive approach. Surah Al-An'am is one of the Meccan surahs that addresses the fundamentals of religion, including monotheism, the message, and resurrection. It was given this name because the word